Pengembangan Soal Evaluasi Pembelajaran Matematika Dengan Pendekatan Deep Learning Dan Tpack Berbasis Wordwall Dalam Meningkatkan Hasil Belajar Kelas Ii Materi Mengnal Bangun Ruang Sd N 2 Belangwetan Tahun Ajaran 2025/2026 - Revina Rahmawati; Afisa Isnaini Irvana; Imroatun Eka Zahra; Putri Zudhah Ferryka (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to develop a wordwall-based mathematics learning evaluation test using a deep learning and TPACK approach in elementary schools. The research method used a descriptive qualitative approach, with data collection techniques through observation and interviews. The results indicate that the wordwall-based evaluation test can improve students' conceptual understanding, motivation, and engagement in mathematics learning. Furthermore, the use of a wordwall makes the evaluation test more interactive and enjoyable. This research is expected to provide an alternative, innovative and effective mathematics learning evaluation test.